ANALISIS PENGARUH PERSEPSI KEMUDAHAN, PERSEPSI RESIKO DAN KUALITAS INFORMASI TERHADAP MINAT MENGGUNAKAN REKENING BERSAMA SHOPEE (Studi Kasus Pada Mahasiswa Fakultas Ilmu Sosial Dan Politik Universitas Pembangunan Nasional “Veteran” Jawa Timur) - Ersaningtyas, Awalina Putri; Susanti, Ety dwi (Jurnal Bisnis Indonesia, 2019)
This type of research is quantitative research. This study uses primary data with online survey methods. The population in this study was  FISIP UPN’V’ JATIM Students who knew and were interested in using an Rekening Bersama Shopee when shopping online. The sample includes some of the FISIP students who are familiar with and interested in using a Rekening Bersama Shopee when shopping online. The sampling technique uses the Lameshow formula. The data analysis technique uses multiple linear regression analysis. Hypothesis testing using the F test and t test. Based on the results of the study show that simultaneously perceived ease (X1), risk perception (X2), information quality (X3) have a significant effect on interest in using (Y) shopee joint accounts. The results also showed that the perception of ease (X1) partially had a positive and significant effect on interest in using Shopee Rekber, risk perception (X2) had a negative and significant effect on interest in using Shopee Rekber, information quality (X3) had a positive and significant effect on interest in using Shopee rekber, and information quality variables have a dominant influence on interest in using Shopee Rekber. Key Word : Perceived Ease of Use, Perceived of Risk, Information Quality, Interest of Using, Rekening Bersama Services (Online Escrow Service in Indonesia) On Shopee.